Expect Nothing: The (Lack of) Influence of Subjective Life Expectancy on Valuation of Child Health States - Lipman, Stefan A. (Frontiers in Health Services, 2022)
Objective Earlier research has shown that individuals' subjective life expectancy (SLE) affects health state valuation with time trade-off (TTO). Individuals with longer expected life durations are less willing to trade-off life duration, which yields higher utilities. In this article, the influence of SLE is explored in the valuation of EQ-5D-Y-3L with a proxy perspective, i.e., adults' valuation of health states considering the life of a 10-year-old child. As SLE for children is likely higher, this might explain earlier findings suggesting that individuals are less willing to trade-off years of life for children than for adults. Methods A total of 197 respondents were recruited to take part in digital TTO interviews, facilitated by trained interviewers. TTO interviews were implemented in accordance with the recommended protocol for the valuation of EQ-5D-Y-3L. Respondents valued 10 EQ-5D-Y-3L health states for a 10-year-old child, after which they were asked to report how old they themselves expected to become and also how old they expected a 10-year-old child to become. Results Generally, adult respondents reported higher SLE for children than for themselves. Neither SLE was systematically associated with the willingness to trade lifetime or the number of life years traded off in TTO tasks. This null-result was substantiated by regression analyses per health state. Conclusion The results of this study suggest that individuals' expectations about longevity are not associated with EQ-5D-Y-3L valuation. This lack of association is in contrast to earlier work and might be explained by the psychological distance introduced with proxy perspective valuation, or by the methodological differences with earlier work.